Trans-(3S, 4S)-Disubstituted pyrrolidines as inhibitors of the human aspartyl protease renin. Part I: Prime site exploration using an amino linker. Issue 8 (15th April 2015) - Lorthiois, Edwige; Cumin, Frederic; Ehrhardt, Claus; Kosaka, Takatoshi; Sellner, Holger; Ostermann, Nils; Francotte, Eric; Wagner, Trixie; Maibaum, Jürgen
Graphical abstract